PENGARUH MOTIVASI DAN PEMBERDAYAAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL PADA DINAS PERTANIAN DAN KEHUTANAN - Sigit Priyanto, 1152020051; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study to examine the influence of motivation and empowerment on performance by mediating organizational commitment. Specific objectives of this study is to examine and analyze whether the mediating role of organizational commitment and empowerment motivational influence on performance. Usefulness of the research is to explain and extend previous research on the influence of motivation, empowerment, and organizational commitment to performance. The study population is an employee Dipertanhut Pemalang as many as 178 people and as many as 178 sample respondents. The research data is the primary data obtained directly from the respondents with the questionnaire. Method research approach with computer software SPSS for Windows version 16. The method of data analysis using Regression Mediation Analisys (MRA) type path analysis. The results showed an interesting empirical conditions to be further investigated as follows: Motivation did notÂ significant impact on organizational commitment; Empowerment positive and significant impact on organizational commitment; Motivation positive and significant effect on kenerja; Empowerment positive and significant effect on the performance; organizational commitment positive and significant effect on the performance; organizational commitment did not mediate the effect of motivation on performance, and organizational commitment did not mediate the effect of empowerment on performance. Keywords: motivation, empowerment, organizational commitment, performance